(untitled) (Academicia Globe: Inderscience Research, 2023)
This article provides information about the role of the People’s Writer of Uzbekistan Shukur Kholmirzayev in modern Uzbek literature, his literary heritage and the importance of his works written during his life, as well as the importance of his profound work. The idea and method of expression, artistic skills described in the stories written by the writer will be revealed. Attention is paid to the problems of studying the biography of the writer’s works. Facts about the real-life background of several characters are presented.